Adolescent sleep quality and quantity and educational attainment: a test of multiple mechanisms using sibling difference models. (25th August 2022) - Kim, Jinho; Park, Gum‐Ryeong; Sutin, Angelina R.
Abstract : Objective: The objective of this study is to determine whether and how sleep quality and quantity during adolescence are related to educational attainment in adulthood. This study also investigates whether this relationship varies by gender. Methods: Using data from the National Longitudinal Study of Adolescent to Adult Health, the present study employed a sibling fixed effect approach that takes into account unobserved family background factors such as genetics and social environments. Gender‐stratified analyses were conducted to consider the potential gendered relationship between adolescent sleep and educational attainment. Results: Controlling for unobserved family‐level heterogeneity attenuated the associations between adolescent sleep characteristics and educational attainment, albeit in different ways for boys and girls. Gender‐stratified models suggest that, for boys, only the association between short sleep duration and educational attainment was robust to adjustment for sibling fixed effects. In contrast, for girls, among three sleep quality measures, only trouble falling or staying asleep remained significantly associated with educational attainment even after controlling for unobserved family heterogeneity. Sibling fixed effects estimates suggest that short sleep duration (6 or fewer hours per night) was negatively associated with years of schooling only among boys ( b  = −0.443), whereas trouble falling or staying asleep was associated with a reduction in years of schooling only among girls ( b  = −0.556). The mechanisms underlying the observed associations also differed by gender. For boys, the association between short sleep duration and educational attainment was partially explained by a combination of educational, social, and psychological factors. Only intermediate educational factors explained part of the association between trouble falling or staying asleep and educational attachment among girls. Conclusions: The study's finding that the relationship between adolescent sleep characteristics and educational attainment and the mechanisms underlying this relationship differ by gender calls attention to the need for gender‐specific interventions.